A Qualitative Assessment of Gender and Irrigation Technology in Kenya and Tanzania. (November 2014) - Njuki, Jemimah; Waithanji, Elizabeth; Sakwa, Beatrice; Kariuki, Juliet; Mukewa, Elizabeth; Ngige, John
Rural household economies dependent on rain-fed agriculture are increasingly turning to irrigation technology solutions to counter weather variability, and guard against low crop yields. Organizations too are using market-based approaches to disseminate technologies to smallholder farmers, and although women are among their target group, little is known of the extent to which these approaches are reaching and benefiting them. There is also scant evidence about the implications for crop choice and income management if these new irrigation technologies are used and controlled by women. This article reports the findings of a qualitative study undertaken in Tanzania and Kenya to examine women's access to and ownership of irrigation pumps, and the implications on their ability to make major decisions on crop choices and use of income from irrigated crops. Results from sales monitoring data showed that less than 10 percent of the pumps are being purchased by women, and most of the major decisions on crop choices and income use continue to be made by men. These findings vary from type of crop, with men making major decisions concerning high-income crops such as tomatoes, and women commanding relatively more autonomy over crops such as leafy vegetables. The study recommends further research to find out whether market-based approaches on their own can guarantee women access to and ownership of technologies, and the specific measures that need to be taken by businesses to achieve the goal of reaching and benefiting women.